ANALISIS EFEKTIVITAS PEMERINTAHAN MUKIM DI KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT PROVINSI ACEH - ANITA SURYA AL-YAHYA (Institut Pemerintahan Dalam Negeri, 2019)
The effectiveness of the Mukim Government in Johan Pahlawan District, West Aceh Regency is an important study in the administration of government activities which oversees several villages and is directly under and responsible to the Camat. Based on the results of the research on the effectiveness of the Mukim Government in general it has not gone well. This is influenced by organizational characteristics; environmental characteristics; factor characteristics of workers; and the characteristics of management policies and practices. The right strategy and priority is based on the SWOT and Litmust Test analysis to improve the effectiveness of the Mukim Government, namely: providing training to increase the capacity of the apparatus; clarify and detail the authority of the Mukim Government through regulation; explore and utilize the potential resources available in the Settlements; provide adequate facilities / parasana; and uti Keywords: Effectiveness, Mukim, Mukim Government, Implementation of Mukim Government